WIMCIT: An in-house development integrated code for neutron analysis in MTR reactors with mixed core - Cuya, Teobaldo (2003)
So far, Peruvian nuclear research reactors RP-10 and RP-0 have been operating only with uranium oxide fuel elements (U3O8+Al). In the future RP-10 reactor will operate with mixed cores (U3Si2+Al, U3O8+Al). For this reason the calculus capacity has to be increased in order to be able to handle the new fuel management. Since preparation of nuclear libraries for diffusion calculation requires a significant amount of computational and human resources a new tool that processes libraries generation and diffusion calculations is necessary.